Performance of Goats as Affected by Replacement of Concentrate Mixture by Maize Hydroponic Fodder - Dhawale, Soniya; Deshmukh, A. D. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted on eighteen growing goats, of around 3-4 months age to evaluate the effect of replacement of concentrate mixture with hydroponically grown maize fodder on performance of goats. Growing goats were fed on three dietary regimes as T0 (control), T1 and T2. Goats in the control group were fed (100%) concentrate mixture while part of concentrate was replaced at 25% by hydroponically grown maize fodder in group T1 and 50% by hydroponically grown maize fodder in T2 group. The dry matter intake, average daily gain and feed conversion efficiency did not show significant variations between the groups. The rumen liquor parameters analyzed monthly revealed non significant variations for pH, NH3-N and significant for TVFA concentrations. The rumen liquor parameters were in the normal range indicated beneficial effects of feeding hydroponically grown maize fodder replacing with the concentrate mixture on rumen and blood biochemical profile of growing goats. The cost of production per kg gain was lower in group fed 25% hydroponically grown maize fodder than that of control and 50% hydroponically grown maize fodder. Thus it is concluded that hydroponic maize fodder can replace concentrate mixture up to 25 percent for economical raising of growing goats.Â